Grammatical features and their Semantic effects in (Al-Hijr) and (Al-Nahl) - Alkhatib, Tasnim; Balajeed, Mariam (Al-Adab Journal, 2023)
From the greatness of the Book of Allah is that its scholars never tire of studying it, and that its wonders are never exhausted. Despite thousands of classes and centuries of study, scholars and researchers continue to dive into its depths of meaning, gathering its pearls, and being amazed by its splendour and beauty. The one who contemplates on the Book of Allah finds a range of different literary features which aid in understanding the text. The following grammatical features are discussed in this study: predication (khabar), negation (nafy) and emphasis (tawkīd), the imperative (amr), the vocative (nidā’), prohibition (nahy), the optative (tarajjī), praise (madḥ) and condemnation (dhamm), the interrogative (istifhām), ishtighāl, the oath (qasam), and the conditional (sharṭ). This study aims to unravel the significance of these grammatical features in the fourteenth part (juz’) of the Qur’an, which consists of Al-Ḥijr and Al-Naḥl, by shedding light on those verses in which these grammatical features are present. The study also shows how these are not superficial features, but rather they signify deep and profound nuances in meaning, which elucidates the beauty of the Qur’anic discourse. The study draws on both the science of grammar (naḥw) and the science of signification (dalālah). It begins with a general introduction to grammatical features, moving on to give detail on each of the features together with examples from the two surahs. The following conclusions are arrived at: (1) That certain grammatical tools and particles, when added to a sentence, add new layers of meaning, since they refine the mood of the sentence, whether it is prohibiting, interrogative, emphasising, etc. (2) That the grammatical features present in part fourteen of the Qur’an give it meanings that are appropriate to the specific context of the discourse.